Political coherence among the domains of food, water, and land in Colombia - Ngaiwi, Mary; Buritica, Alexander; Castro, Augusto (2024)
This study analyzes the coherence of policies in the land, water, and food sectors, focusing on their alignment, resource allocation, and implementation challenges. We find that there is high internal coherence across sectors, with strong alignment between policy instruments and overarching objectives. However, gaps remain, particularly in the food sector, where policies lack scope and depth. There is also strong external coherence between policy instruments and target populations, but higher-level objectives in the food and water sectors are less developed. One significant issue is the discrepancy in resource allocation within the food sector; despite the importance of food production policies, low investment limits their impact. In the land sector, the Multipurpose Cadastre policy faces implementation challenges due to the absence of a clear roadmap, hindering governance improvements. Additionally, efforts to combat deforestation focus on sustainable production and forest conservation but neglect initiatives aimed at preventing and prosecuting illegal activities. This study emphasizes the need for enhanced resource allocation and comprehensive policy implementation to achieve effective governance and sustainability in these critical sectors.